Kearifan Lokal Masyarakat Pesisir dalam Memahami Teknologi Hasil Perikanan - Dati Nawastuti (Jurnal Maksipreneur, 2018)
Characteristics of people in coastal area are taught and open mind like sea which is analog to open access and high risk. They inherit knowledge from their ancestors who refered to stars constelation as guide, besides other traditional technologies. There are four research questions: (1) How are technologies inherited to young generations? (2) Are the developing fish technologies accepted? (3) What are governments’, scholars’, and NGO’s roles? and (4) How is people’s responds towards modern technologies? Meanwhile, this research wants: (1) To know inheritance technologies, (2) To understand acceptability level, (3) To explore the roles’ of governments, NGOs, and scholars, and (4) To recognize people’s respond toward technologies. Fisheries commodities have comparative advance, although they are perishable food that need quick, accurate, and right treatment. The research was conducted in Larantuka Sub-district of East Flores. Observation and interview were data collection methods applied in this research. Data were analysed using SWOT analysis. It is concluded that traditional technologies are useful to preserve local culture and wisdom. The role of government through local development agents, NGOs, and scholars via trainning has not applicable yet for the community in the wide area and has limitations of man power.